Individualized conservative therapeutic strategies for adenomyosis with the aim of preserving fertility - Han, Lei; Liu, Yanni; Lao, Kaixue; Jiang, Jianxi; Zhang, Caiying; Wang, Yanlin (Frontiers in Medicine, 2023)
Adenomyosis is a diffuse or localized organic disease caused by benign invasion of endometrial glands and stroma into the myometrium. It is a common disease that seriously affects reproductive health of women in childbearing age. Due to the unknown etiology and pathophysiological mechanism, and the lack of unified diagnostic criteria and effective treatment methods, total or subtotal hysterectomy has become a radical treatment for adenomyosis, which will lead to the complete loss of fertility. With the continuous exploration of the treatment to adenomyotic patients who have infertility or fertility intentions, new drugs, surgical methods and treating concepts appears. Adopt individualized conservative therapeutic strategies for patients with different conditions, preserve the uterus as much as possible and protect the patient’s fertility, which will play an important role on the follow-up assisted reproductive treatment and long-term management of adenomyosis.